What it Takes to Return : UN Peacekeeping and the Safe Return of Displaced People - Bove, Vincenzo; Di Salvatore, Jessica; Elia, Leandro (World Bank, Washington, DC, 2022)
Can the international community enable conditions for voluntary, safe and sustainable return of displaced people As conflict is key in the decision to leave and to return, this paper investigates whether the deployment of UN peacekeeping operations can reduce the insecurities driving displacement and delaying return. It explores the case of South Sudan, which hosts the second largest UN peace operation in the world. It combines information on peacekeepers' subnational deployment with data on individuals' intention to move and host communities' perceptions of returnees and internally displaced people (IDPs) using two surveys, one carried out between 2015 and 2017 and one in 2018. To mitigate concerns about non-random subnational assignment of peacekeepers, the paper exploits variations in the presence of previous infrastructures and information on the total supply of troops to African countries from each troop-contributing country. The paper finds that UN peacekeeping affects both the magnitude and the quality of return. Displaced people are more likely to return home if peacekeepers are deployed in their county of destination. At the same time, the local presence of peacekeepers mitigates host communities' negative perception of IDPs; they also enable the delivery of support to communities that seem to improve attitudes toward returnees and IDPs.